Validation of the traditional Chinese version of the prolapse quality of life questionnaire (P-QOL) in a Mandarin-speaking Taiwanese population - Fei-Chi Chuang; Li-Ching Chu; Fu-Tsai Kung; Kuan-Hui Huang (Elsevier, 2016)
Objective: To validate the traditional Chinese translated version of the prolapse quality of life questionnaire (P-QOL). Materials and Methods: The P-QOL questionnaire was translated into traditional Chinese characters and administered to women recruited from gynecologic outpatient clinics of Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, Taiwan. After the test-retest reliability and internal consistency were established in a pilot study, all participants completed the P-QOL questionnaire and were examined in the lithotomy position using the Pelvic Organ Prolapse Quantification System (POP-Q). The construct validity was assessed by comparing symptom scores and quality-of-life domain scores between symptomatic and asymptomatic women. Results: Of the 244 women recruited, 159 were symptomatic for pelvic organ prolapse, and 85 were asymptomatic. The test-retest reliability confirmed a significant positive monotonic correlation between the total scores of each domain (n = 30, Spearman's rho was from 0.411 to 0.888, p < 0.05 of all). All items achieved a Cronbach α > 0.80 showing good internal consistency. Among the 18 symptom questions, the scores differed significantly between symptomatic and asymptomatic women for 12/18 symptom questions. These 12 questions referred to the prolapse/vaginal symptoms. All the quality of life domains differed significantly (p < 0.05) between symptomatic and asymptomatic women except for the domain of sleep/energy (p = 0.108). Conclusion: The traditional Chinese language version of the P-QOL is a reliable instrument for the assessment of symptom severity and impact on quality of life in women with pelvic organ prolapse.